Sprouting and genetic structure vary with flood disturbance in the tropical riverine paperbark tree, Melaleuca leucadendra (Myrtaceae)1. Issue 11 (1st November 2013) - Chong, Caroline; Edwards, Will; Pearson, Richard; Waycott, Michelle
Abstract : Premise of the study: Sprouting in woody plants promotes persistence in the face of disturbance, ultimately influencing population structure. Different disturbance regimes drive variable population responses, but there have been few direct tests of the relative differences in population structure to specific drivers. We measured population structure as genotypic diversity (clonality) as a function of hydrological regime for a riverine tree, Melaleuca leucadendra, a major structural component in flood landscapes in the Australian dry tropics. Methods: We estimated clonality, genotypic richness, and population allelic diversity. The relationship among disturbance, genetic estimates of clonality, and population distinctiveness was compared with flood regime, characterized by return frequencies and hydrological stress at individual river reaches. Key results: Two contrasting patterns of genotypic structure were detected and corresponded to order‐of‐magnitude differences in flood regime between sites. At mainstem locations characterized by greatest flood intensity, sprouting generated clonal structure to 17 m (30% ramets clonal). By contrast, clonality was atypical at lower‐disturbance tributaries (0% clonal). Population allelic distributions showed extensive genetic exchange among mainstem locations, but strong genetic differentiation between mainstem and tributaries. Conclusions: Population structure and distinctiveness in riverine Melaleuca are determined by differences in sprouting and recruitment responses that depend on localized hydrological regime. Sprouting contributes to population persistence via localized clonal growth. Resprouting following disturbance in M. leucadendra may help explain its numerical dominance in tropical river systems. This study, although preliminary, suggests that flood ecosystems may represent excellent experimental systems to develop a better understanding of whole‐organism responses to environmental drivers.